The Potential of Cocos nucifera Leaf Fibers as an Adsorbent for Physical Oil Spill Remediation and the Effect of Particle Size on its Sorption Efficiency and Capacity - Agunod, Edrich Johnmyr R. (Animo Repository, 2022)
Due to oil spills being deemed a consistent problem in the foreseeable future, sustainable methods to address oil spills must be developed to prevent long-term damage to the environment and to address oil spills efficiently. Commercial adsorbents, despite their efficiency and reusability, cause damage to the environment in their continuous use. Commercial adsorbents are non-biodegradable and are extensively modified chemically, posing environmental concerns. Inspired by studies testing the potential of abundant Date palm fibers in the Middle East, the researchers aim to observe the potential of Cocos nucifera leaf fibers for the physical remediation of oil spills. The study aims to calculate the oil sorption efficiency and capacity of the Cocos nucifera leaf fibers in physical oil remediation and to determine its relationship to particle size. To observe the potential of Cocos nucifera as an adsorbent, the researchers will adapt the methodology of Abdelwahab et al. (2017) to determine the fiber’s sorption efficiency and capacity, as well as its relationship to particle size. Although the gathered values for sorption efficiency show negligible results, Cocos nucifera as an adsorbent for physical oil spill remediation showed promising results in terms of its sorption capacity. The values gathered showed that the fibers can adsorb at least more than half their weight (56.7%) for 1.6mm, up to almost double their weight (197%) for 2.5mm. In general, the adsorbent leaf fibers can adsorb slightly more than their weight, with an average sorption capacity of 1.07g of oil per gram of adsorbent.